Antibody responses against heterologous A/H5N1 strains for an MF59-adjuvanted cell culture–derived A/H5N1 (aH5N1c) influenza vaccine in healthy pediatric subjects - Chanthavanich, Pornthep; Versage, Eve; Van Twuijver, Esther; Hohenboken, Matthew (Vaccine, 2021)
•MF59-adjuvanted, cell-based flu vaccine (aH5N1c) may be advantageous in a pandemic.•aH5N1c elicited robust antibody responses to heterologous A/H5N1 strains.•Responses were higher when assayed with microneutralization than HI. Vaccines are the main prophylactic measure against pandemic influenza. Adjuvanted, cell culture–derived vaccines, which are not subject to limitations of egg-based vaccine production, have the potential to elicit an antibody response against heterologous strains and may be beneficial in the event of an A/H5N1 pandemic. A prespecified exploratory analysis of data from a phase 2, randomized, controlled, observer-blind multicenter trial (NCT01776554) to evaluate the immunogenicity of a MF59-adjuvanted, cell culture–based A/H5N1 influenza vaccine (aH5N1c), containing 7.5 µg hemagglutinin antigen per dose, in subjects 6 months through 17 years of age was conducted. Geometric mean titers (GMT) were determined using hemagglutination inhibition (HI) and microneutralization (MN) assays, and proportions of patients achieving seroconversion, HI and MN titers ≥ 1:40, and a 4-fold increase in MN titers against 5 heterologous strains (influenza A/H5N1 Anhui/2005, Egypt/2010, Hubei/2010, Indonesia/2005, and Vietnam/1203/2004) three weeks after administration of the second dose were assessed. After the second dose, HI GMTs against heterologous strains increased between 8- and 40-fold, and MN GMTs increased 13- to 160-fold on Day 43 vs Day 1. On Day 43, 32–72% of subjects had HI titers ≥ 1:40 and achieved seroconversion against the heterologous strains. Using the MN assay, 84–100% of subjects had MN titers ≥ 1:40 and 83–100% achieved an at least 4-fold increase in MN titers against the heterologous strains. The highest responses were consistently against A/H5N1 Egypt/2010. When given to children aged 6 months through 17 years, aH5N1c resulted in increased immunogenicity from baseline against all 5 heterologous A/H5N1 strains tested, demonstrating the potential of an MF59-adjuvanted, cell-derived A/H5N1 vaccine to provide cross-protection against other A/H5N1 strains (NCT01776554).